The innovation of Baroque architectural style as experimentation of non-euclidean metrics (II and XVII-XVIII c.) - Moneti, Andrea (ROMULA, 2023)
New exam of the peculiar case of dialectics between compositional laws and stylistic innovation of the transition from classicism to baroque. Applying categories of differential geometry to the geometry of the architectural spaces created by the two styles, it is possible to construe that classicism expressed them as metric Euclidean spaces, and baroque as non-Euclidean ones. This can lead to analyze this specific transition as an example of innovation through a coherent overturning of laws however always valid. This can suggest the use of this method in other cases in architectural history.